The case for incorporating CSR into strategy and the joint role with Marketing in promoting sustainable consumption and production. - Ikiao, Timothy (2015)
Through this paper, we attempt to fill investigate how marketing, or elements of it, relate to the general social agenda and whether there is an overarching plan that directly or indirectly connects the two. We will do this by looking at what various scholars have written on each of these particular topics and also those who have previously attempted to relate the two. In the course of this, we will also see whether the terms corporate social responsibility tie together with sustainability and also mention some recent developments at the global stage that have created a clear vision and set goals for the world regarding sustainability. We shall therefore find out the place and role of marketing and sustainability in a company’s strategy, whether marketing and sustainability intersect or interact and how do they do this and whether messaging in advertisements for sustainable products varies from those of conventional products.